Bond strength assessment of a universal adhesive system in etch-and-rinse and self-etch modes - Gustavo do Prado SCHOENHALS; Cinthia Lais BERFT; Fabiana Scarparo NAUFEL; Vera Lucia SCHMITT; Larissa Pinceli CHAVES (Universidade Estadual Paulista, 2019)
Abstract Introduction Modern dentistry is reflected in the insertion of new materials with different adhesion forms in dental structures, such as the Universal adhesive system. Objective To evaluate the bond strength of the universal dentin adhesive system, in the form of self-etching and conventional application, compared with a simplified conventional adhesive system, in two distinct periods: 1 week and 6 months. Material and method 48 bovine incisors separated into 6 groups, stored for 7 days, were selected. Worn out the buccal enamel until dentin exposure. Adper Single Bond 2 (3M Espe) or SingleBond Universal (3M Espe) adhesives were applied, and catheters filled with Opallis Flow (FGM) composite were placed. After photoactivation, the catheters were removed and the specimens (n = 48), stored in distilled water at 37 °C for one week and six months, were exposed. The specimens were fixed to a universal testing machine (EMIC DL 2000) with a speed of 0.5 mm / min. Bond strength (BS) was calculated in MPa, and data were statistically analyzed by Anova and Tukey test at 5% significance level. Result For Adper Single bond, the BS was equivalent in the times tested; for Universal conventional and self-conditioning time influenced the BS, with a decrease in the results. At 1 week, all stickers were different from each other, with higher BS for Universal conventional mode, followed by universal self-etching mode and then Adper Single bond. Conclusion The best results were achieved with universal adhesive in conventional mode for both tested times.